Electrocardiography as an early cardiac screening test in children with mitochondrial disease - Ran Baik; Jung Hyun Chae; Young Mock Lee; Hoon Chul Kang; Joon Soo Lee; Heung Dong Kim (Korean Pediatric Society, 2010)
PurposeTo evaluate myocardial conductivity to understand cardiac involvement in patients with mitochondrial disease.MethodsWe performed retrospective study on fifty-seven nonspecific mitochondrial encephalopathy patients with no clinical cardiac manifestations. The patients were diagnosed with mitochondrial respiratory chain complex defects through biochemical enzyme assays of muscle tissue. We performed standard 12-lead electrocardiography (ECG) on all patients.ResultsECG abnormalities were observed in 30 patients (52.6%). Prolongation of the QTc interval (>440 ms) was seen in 19 patients (33.3%), widening of the corrected QRS interval in 15 (26.3%), and bundle branch block in four (7.0%). Atrioventricular block, premature atrial contraction and premature ventricular contraction were seen in two patients each (3.5%) and Wolff-Parkinson-White syndrome in one patient (1.8%).ConclusionGiven this finding, we recommend active screening with ECG in patients with mitochondrial disease even in patients without obvious cardiac manifestation.